2007
DOI: 10.1039/b703415f
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic modelling of the oxidation of large aliphatic hydrocarbons using an automatic mechanism generation

Abstract: A mechanism generator code to automatically generate mechanisms for the oxidation of large hydrocarbons has been successfully modified and considerably expanded in this work. The modification was through (1) improvement of the existing rules such as cyclic-ether reactions and aldehyde reactions, (2) inclusion of some additional rules to the code, such as ketone reactions, hydroperoxy cyclic-ether formations and additional reactions of alkenes, (3) inclusion of small oxygenates, produced by the code but not inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 29 publications
1
27
0
2
Order By: Relevance
“…Nehse et al [36] developed detailed kinetic reaction mechanisms for n-decane and n-heptane to simulate intermediate temperature shock tube experiments for both fuels. A recent study [37] demonstrated the capability to generate detailed kinetic mechanisms for alkane fuels of any desired size and illustrated this by analyzing experimental data for n-hexadecane.…”
Section: Previous Workmentioning
confidence: 98%
“…Nehse et al [36] developed detailed kinetic reaction mechanisms for n-decane and n-heptane to simulate intermediate temperature shock tube experiments for both fuels. A recent study [37] demonstrated the capability to generate detailed kinetic mechanisms for alkane fuels of any desired size and illustrated this by analyzing experimental data for n-hexadecane.…”
Section: Previous Workmentioning
confidence: 98%
“…Alkana rantai lurus cenderung mudah terbakar, sedangkan alkana rantai beracabang dan senyawa aromatik cenderung sulit terbakar. Senyawa-senyawa yang analog seperti n-pentana, n-heksana, n-heptana, n-oktana, n-nonana dan n-dekana memiliki profil dan waktu tunda ignisi yang hampir sama (Muharam, 2005) pada rasio ekuivalensi dan rentang temperatur dan tekanan awal yang sama. Oleh karena itu, untuk mengetahui karakteristik pembakaran BBK, pengetahuan tentang pembakaran komponen bahan bakar tersebut sangat diperlukan.…”
Section: Pendahuluanunclassified
“…The detailed reaction mechanism of LGV was derived from the detailed reaction mechanism for large aliphatic hydrocarbons developed by Muharam [7]. The validation was performed by comparing the calculated results of ignition delay time with the experimental data of ignition delay time for pure propane and pure n-butane.…”
Section: Methodsmentioning
confidence: 99%